Combined Brain-Perfusion SPECT and EEG Measurements Suggest Distinct Strategies for Speech Comprehension in CI Users With Higher and Lower Performance - Kessler, Mariella; Schierholz, Irina; Mamach, Martin; Wilke, Florian; Hahne, Anja; Büchner, Andreas; Geworski, Lilli; Bengel, Frank M.; Sandmann, Pascale; Berding, Georg (Frontiers in Neuroscience, 2020)
Cochlear implantation constitutes a successful therapy of inner ear deafness, with the majority of patients showing good outcomes. There is, however, still some unexplained variability in outcomes with a number of cochlear-implant (CI) users, showing major limitations in speech comprehension. The current study used a multimodal diagnostic approach combining single-photon emission computed tomography (SPECT) and electroencephalography (EEG) to examine the mechanisms underlying speech processing in postlingually deafened CI users (N=21). In one session, the participants performed a speech discrimination task, during which a 96-channel EEG was recorded and the perfusions marker 99mTc-HMPAO was injected intravenously. The SPECT scan was acquired 1.5 hours after injection to measure the cortical activity during the speech task. The second session included a SPECT scan after injection without stimulation at rest. Analysis of EEG and SPECT data showed N400 and P600 event-related potentials (ERPs) particularly evoked by semantic violations in the sentences, and enhanced perfusion in a temporo-frontal network during task compared to rest, involving the auditory cortex bilaterally and Broca’s area. Moreover, higher performance in testing for word recognition and verbal intelligence strongly correlated to the activation in this network during the speech task. However, comparing CI users with lower and higher speech intelligibility (median split with cutoff + 7.6 dB SNR in the Göttinger sentence test) revealed for CI users with higher performance additional activations of parietal and occipital regions, and for those with lower performance stronger activation of superior frontal areas. Further, SPECT activity was tightly coupled with EEG and cognitive abilities, as indicated by correlations between 1) cortical activation and the amplitudes in EEG, N400 (temporal and occipital areas) / P600 (parietal and occipital areas), and 2) between cortical activation in left-sided temporal and bilateral occipital/parietal areas and working memory capacity. These results suggest the recruitment of a temporo-frontal network in CI users during speech processing and a close connection between ERP effects and cortical activation in CI users. The observed differences in speech-evoked cortical activation patterns for CI users with higher and lower speech intelligibility suggest distinct processing strategies during speech rehabilitation with CI.